2008
DOI: 10.1109/icassp.2008.4517659
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive RR prediction for cardiac MRI

Abstract: Cardiac magnetic resonance imaging (MRI) is very challenging due to the perpetual heart movements. This movement is pseudo-periodic and implies several issues for image acquisition. Building a single image requires several shots, done on a specific timing of the cardiac cycle. Nowadays the heart rate is estimated before imaging and then it is assumed not to evolve during acquisition. Additionally, in order to remove motion artifacts, the patients are asked to perform breathholds. Unfortunately, while performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…These estimates could be used for a semi-online filtering of the MR-ECG, where the delayed impulse response estimations are used to filter in real-time the MFG command signals for MFG artifact suppression. An online phase assignment procedure is also conceivable, by using a RR interval prediction [12]. The unification of ECG and MFG models for Bayesian filtering overcomes state-of-the-art MR-ECG signal processing limitations and opens the way of accurate interpretation during a complete MRI examination.…”
Section: Discussionmentioning
confidence: 99%
“…These estimates could be used for a semi-online filtering of the MR-ECG, where the delayed impulse response estimations are used to filter in real-time the MFG command signals for MFG artifact suppression. An online phase assignment procedure is also conceivable, by using a RR interval prediction [12]. The unification of ECG and MFG models for Bayesian filtering overcomes state-of-the-art MR-ECG signal processing limitations and opens the way of accurate interpretation during a complete MRI examination.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3. The second order has been chosen because it is a good compromise between accurate prediction and computational efficiency (21) and allows real‐time processing. Setting the model to an higher order will improve accuracy of the prediction but lengthen the computation and convergence times.…”
Section: Methodsmentioning
confidence: 99%
“…Our hypothesis is that most people make small movements while they are holding their breath, yielding thoracic volume variations that could modify the RR interval variation patterns. Moreover, a previous study (21) has reported some prediction improvements when using respiratory signals in breath‐hold.…”
Section: Theorymentioning
confidence: 95%
See 2 more Smart Citations